Metals in wastes - Ismael, Maria Rosinda C.; Kwaśniewska, Dobrawa; Regel-Rosocka, Magdalena; Reis, Maria Teresa A.; Rzelewska, Martyna; Staszak, Katarzyna; Staszak, Maciej; Tylkowski, Bartosz; Wieczorek, Daria; Wieszczycka, Karolina (De Gruyter, 2018)
Metals in Wastes is an excellent guide for scientists, students, engineers, chemists, and industrial chemists who are looking for knowledge of the main sources of metals in industrial wastes. Metals are valuable materials that can be recycled again and again without degrading their properties. The recycling of metals enables us to preserve natural resources while requiring less energy to process than the manufacture of new products using virgin raw materials. A team of experts reviews the state-of-the-art and provides the readers not only with a comprehensive in-depth overview of the main composition of wastes but also discloses innovative methods which have been applied for recovery of critical and valuable metals in petrochemical industry, rubber, energy and automotive industries. This know-how could be considered as a useful reference tool for moving towards the zero-waste economy. Additionally, the book describes the economic aspects of metals recovery from various sources. This is essential for those already involved in the metals business and also for the financial, investment and advisory community internationally.